Studies of Botrytis cinerea causing botrytis gray mold disease in chickpea (Cicer arietinum L.) (Journal of Bio-Science, 2016)
Context: To investigate the morphological and pathological information on causal organism Botrytis cinerea for better understanding of the infection process and controlling outbreaks of the most damaging disease, Botrytis Gray Mold (BGM),of chickpea.Objectives: To study the cultural and morphological characteristics and growth requirements of Botrytis cinerea Pers. ex. Fr. This study was also aimed to know about the cytological and genetic behavior of B. cinerea in relation to its pathogenicity and the infection process on chickpea.Materials and Methods: A total of 83 isolates of Botrytis cinerea Pers. ex. Fr. collected from the major chickpea growing areas of Bangladesh were studied under 5 and 2 different groups based on their cultural and morphological characteristics, respectively. Four different types of isolates were observed and characterized considering the arrangement of sclerotia by growing them on PDA. Cultural characteristics such as colony color, shape, margin and texture of B. cinerea isolates were observed on the prepared PDA medium. Morphological characteristics in terms of sclerotia color, shape and size, ability of sclerotia production and their arrangement were observed on PDA medium after three days of incubation at 20°C. The prepared samples were placed in a platinum coater providing 10 mA current flow and then placed into the Scanning Electron Microscope (SEM) for obtaining the image. The conidial observation was taken using aqua suspension under the fluorescence microscope at 19V/100W. SEM observation was made to study the infection process of B. cinerea. Data on quantitative and qualitative cultural characteristics were put into analytical software 'SPSS 11.5 for Windows' and nonhierarchical clustering was performed.Results: The mean sizes of five isolates of B. cinerea were 8.02-12.3x 5.1-9.0 ?m (volume 158.12-445.38 ?m3). The pathogen B. cinerea grew well on malt-extract agar (MEA) and chickpea dextrose agar (CDA) medium. The highest (81.26 mm) average mycelial radial growth was obtained on MEA followed by CDA (81.11 mm). Maximum disease in the shortest incubation period was produced with the inoculum concentration of 2.5×104. More pathogenicity and higher disease score was performed by the isolates containing higher mean number of nucleus per conidia than the isolates containing lower values. Optimum temperature and incubation time for conidial germination was observed at 20°C and 24 h, respectively. More than 90% relative humidity was needed for the germination of B. cinerea conidia. B. cinerea survived in all plant parts up to next cropping season. Sclerotia of B. cinerea were also found to survive in the soil up to 9 months. All the 5 isolates of B. cinerea remained viable after 3 years of storage in sterile water at -80°C and in sand at 4°C with same pathogenicity.Conclusion: The cyto-pathological observations including cultural and morphological information of the causal pathogen B. cinerea might be useful in controlling the outbreaks of the disease BGM and ultimately reducing the yield loss of the valuable crop chickpea.J. bio-sci. 22: 69-76, 2014